Analysis by Enzyme-Linked Immunosorbent Assay and PCR of Human Liver Abscess Aspirates from Patients in China for Entamoeba histolytica - Zengzhu, G. (American Society for Microbiology, 1999)
Aspirates of liver abscesses were analyzed for Entamoeba histolytica. PCR detected a gene encoding a 30-kDa protein in all samples but detected the ribosomal DNA gene in only 14 (33.3%) samples. Enzyme-linked immunosorbent assay detected antigen in 41 (97.6%) samples. PCR analysis of a strain-specific antigen (SSG) revealed that abscesses were caused by various strains.